A combined method of oral commissure lifting for perioral rejuvenation in Asians. Issue 12 (December 2020) - Pan, Bailin; Zhao, Runlei; Wu, Siqiao; Lin, Hengju; Long, Yan; Hao, Guang; Chen, Jing; Nian, Fuhong
Summary: Background: A drooping oral commissure shows an appearance of ageing and sadness. To improve it with less complications has become a rising aesthetic concern for Asians. Objectives: To share our method for oral commissure lifting by a combined technique including skin resection, oral commissure suspension, and dissection of the depressor anguli oris muscle (DAO), and to present the follow-up outcomes. Methods: This was a retrospective study of patients who underwent oral commissure lifting between 10/2012 and 03/2019 at the Department of Plastic Surgery, Peking University Third Hospital. The patients were routinely followed at 1 week, 1 month, and over 6 months. After operation, cases with the cheilions (oral commissure points) located above the ipsilateral lateral thickening points were considered to be effective, with the points at the same level were considered to be mildly effective, and with the cheilions below the ipsilateral lateral thickening points were considered to be ineffective treatment. Results: Surgery took around an hour. Swelling subsided within 9.2±3.4 days. The red color of the scar disappeared within 3.7±1.5 months and the natural facial expression was restored within 7.9±2.6 weeks. Among the 159 cases, 125 (78.6%) were obviously effective, 21 (13.2%) were mildly effective, and 13 (8.2%) were ineffective. After the first operation, 112 patients (70.4%) were satisfied, 39 patients (24.5%) were basically satisfied, and eight patients (5.0%) were unsatisfied. Conclusions: The combined technique for the oral commissure lifting displayed a significant effect with little complication in Asian patients.